1979
DOI: 10.1093/ageing/8.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Dysrhythmias in Apparently Healthy Elderly Subjects

Abstract: Using 24-hour ambulatory electrocardiographic (ECG) monitoring, the incidence of cardiac dysrhythmias was investigated in 50 apparently healthy elderly subjects aged over 60 years. There was a high incidence of both ventricular and supraventricular ectopic beats, supraventricular tachycardia and sinus arrest. First- and second-degree block were also noted. The incidence of dysrhythmias bore no obvious relationship to age over 60, sex, blood presssure, cigarette smoking, caffeine and theophylline ingestion or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Cardiac disease is common in elderly patients, and cardiac arrhythmias occur more frequently in the elderly than at younger ages 1 . The prognostic significance of asymptomatic cardiac arrhythmias in old persons is unclear, and more studies are needed to define their importance 2 Glasser et al found that the high incidence of “benign” slow atrial tachycardias they observed in an older population could not be related clearly to frank cardiac disease 3 . For their 13 subjects, the average age was only 69 years—considerably less than that in our group (83 years)—and follow‐up was not reported.…”
Section: Discussionmentioning
confidence: 51%
“…Cardiac disease is common in elderly patients, and cardiac arrhythmias occur more frequently in the elderly than at younger ages 1 . The prognostic significance of asymptomatic cardiac arrhythmias in old persons is unclear, and more studies are needed to define their importance 2 Glasser et al found that the high incidence of “benign” slow atrial tachycardias they observed in an older population could not be related clearly to frank cardiac disease 3 . For their 13 subjects, the average age was only 69 years—considerably less than that in our group (83 years)—and follow‐up was not reported.…”
Section: Discussionmentioning
confidence: 51%
“…Reported proportions hitherto have been between 8 and 62% [4,5,[7][8][9][10]15], This finding suggests that multifocal VPBs are of 'benign' value. Bjerregaard [3] pro posed that more than two types of configura tion would count as 'abnormal'.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly long-term follow-up of patients is needed to determine the prognostic importance of arrhythmias detected at initial examination along the lines of the early studies by Hinkle," 33 but using modern automated equipment for analysing the tapes: at least one group of investigators plans to do this. 32 What does all this mean in terms of finding premature contractions on an ambulatory tape ? In symptomatic patients recordings may help to establish the nature of the arrhythmia underlying palpitations, and in those with coronary artery disease they may help separate a high risk group.…”
Section: Ventricular Premature Beats -Stormy Petrels?mentioning
confidence: 99%